TQM Awareness among Civil Servants in the Education Sector - Gandil, Leslie Tawan (1996)
This study attempts to investigate the correlation of TQM awareness among the civil servants in the State Education Headquarters in Kuching, Sarawak. Specifically, the study attempted to find out the relationship between the TQM awareness with the gender, age, ethnic group, marital status, education qualification, job position, length of service and department sector/section of the respondents. The units of analysis were the staff of the education department from all eight sectors and sections, male and female. The research methodology utilised was a survey based on a personally distributed questionnaire which incorporately ued Likert Scales. The resultant information was analysed by applying the statistical tools and techniques including t-Test, one-way ANOVA, Pearson Correlation Analysis and Multiple Regression to determine the significance of the relationship of the items under investigation with TQM awareness. The study was motivated by the interest of the researcher following the introduction of TQM in the civil service since 1992. The TQM principles emphasized in the circular were: (1) Top management support, (2) Strategic Quality Planning, (3) Customer focus, (4) Teamwork, (5) Training and recognition, (6) Performance measurement, and (7) Quality assurance. The major findings of the study revealed that there was no difference in the TQM awareness perceived by male and female staff. The findings further showed that the staff perceived equal TQM awareness irrespective of their age, ethnic group, marital status, length of service and departmental sectors/sections they belonged to. However, the educational qualification and job position of the respondents did indicate a positive and significant relationship with the TQM awareness. The findings further elaborated that all the seven TQM principles had shown positive and significant correlation with the TQM awareness. The best predictor of the TQM awareness as team work followed by (in order) customer focus, quality assurance, training and recognition, strategic quality planning, performance measurement and top management support. The findings concluded that educational qualification and job positions were inter-related. Those who were graduates held the post of at least lower management. Generally, it was this management group that showed positive TQM awareness with respect to their educational qualification and job position in the department.